PERANCANGAN SISTEM INFORMASI PENGADUAN PELANGGAN BAGIAN CATER PT PLN CABANG UPJ BEKASI KOTA - Sutedjo, Eddy; Lie, Sui (CommIT (Communication and Information Technology) Journal, 2007)
Article discusses the design of user complaint information system on Cater PLN Company Branch UPJ CityBekasi. The design systems consist of complaint acceptance module, scheduled module, field team determinationmodule, and complaint report module. This information system application program testing of user complaint isusing black-box testing method. Black-box testing method was done by giving a number of inputs to the applicationprogram that later processed suitable with the functional needs to produce the needed output. The research resultis the program able to give information about the complaint faster, accurate, and up to date compared to the use ofmanual document.Keywords: information system, customer